Global, regional, and national epidemiology of type 1 diabetes in children from 1990 to 2021: trend and health inequality analyses based on the Global Burden of Disease Study 2021 - Jing Xie; Weilan Li; Xiaomin Li; Xueli Zhang; Jing Liu; Zeye Liu; Shenqi Jing; Hua Shao (Diabetology & Metabolic Syndrome)
Abstract Background Type 1 diabetes (T1D) is a significant health challenge for children. Assessing the epidemiological patterns and health inequalities associated with T1D at the global, regional, and national levels, along with future projections, is essential for informing equitable public health policies. Methods Based on the Global Burden of Disease (GBD) 2021 database, this study examined trends in the incidence, prevalence, disability-adjusted life years (DALYs), and mortality of T1D in children aged 0–14 years. Attribution decomposition analysis was used to explore the main drivers of the changes in the T1D burden, including the effects of population growth, epidemiological changes, and fertility rates. Regression models and concentration curves were employed to evaluate health inequality among countries and regions with different sociodemographic index (SDI) levels, and predictive models were used to estimate future trends of T1D over the next 30 years. Results From 1990 to 2021, the global incidence and prevalence of T1D increased significantly, by 32.04% and 41.47%, respectively, whereas the global DALY and mortality rates decreased by 18.33% and 24.83%, respectively. Attribution decomposition analysis revealed that population growth and epidemiological improvements were the main drivers of the changes in the T1D burden. DALYs and mortality decreased significantly in high-SDI countries, whereas health inequality remained severe in low-SDI countries. The predictive models indicate that the incidence and prevalence of T1D among children worldwide will continue to rise in the coming decades, particularly among males. By 2050, DALYs and mortality are expected to decline further. Conclusion Although the global T1D burden has increased, advances in medical technology, especially in high-SDI countries, have alleviated its health impacts. To reduce global health inequality, low-SDI countries must strengthen international cooperation by improving T1D prevention and control through resource sharing and the introduction of medical technologies.